Ethics and moral reasoning : a student's guide - Mitchell, C. Ben (Wheaton, Illinois : Crossway, 2013)
From drone warfare to gay marriage, the modern world is full of ethical conundrums stemming from a plethora of amazing technological advances and dramatic cultural shifts. Challenging the relativism so rampant in our society today, C. Ben Mitchell helps us thoughtfully engage our morally confused world in this introduction to ethics from a distinctly Christian perspective. Drawing on insights from key historical figures and modern Christian ethicists such as Stanley Hauerwas and N. T. Wright, this book will help you embrace a holistic approach to moral reasoning that is founded on Scripture and informed by history.
Introduction: Why Ethics Matter -- 1. The challenges of a relativistic world -- 2. The history of moral reasoning, part 1 -- 3. The history of moral reasoning, part 2 -- 4. Enlightenment ethics -- 5. Evangelical ethics -- 6. Using the Bible in moral decision making.
Includes bibliographical references (pages 106-107) and indexes.
Keywords: Christian ethics